Electrode material, and electrode, membrane electrode assembly, and solid polymer electrolyte fuel cell using the same

A mesoporous carbon-based electrode material with a tantalum carrier metal support system addresses carbon corrosion issues in PEFCs, ensuring stable Pt catalyst performance and improved durability.

JP7613757B2Active Publication Date: 2025-01-15KYUSHU UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2022152125
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-09-26
Publication Date
2025-01-15
Estimated Expiration
2042-09-26

AI Technical Summary

Technical Problem

Carbon-based electrode materials in polymer electrolyte fuel cells (PEFCs) suffer from carbon corrosion due to the acidic environment, leading to Pt particle agglomeration and shedding, which reduces fuel cell performance and durability.

Method used

The use of a porous composite carrier made of mesoporous carbon with a carrier metal, such as tantalum, fixed to the inner and outer surfaces of the carbon pores, supporting electrode catalyst particles, which prevents direct contact between Pt and carbon, thereby inhibiting carbon corrosion and agglomeration.

Benefits of technology

The proposed electrode material enhances the durability and performance of PEFCs by maintaining the stability of Pt catalyst particles, even under varying operational conditions, including start-up and load fluctuations.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007613757000002
    Figure 0007613757000002
  • Figure 0007613757000003
    Figure 0007613757000003
  • Figure 0007613757000004
    Figure 0007613757000004
Patent Text Reader

Abstract

To provide an electrode material capable of providing a fuel cell electrode having excellent electrode performance and durability.SOLUTION: An electrode material includes a carrier skeleton made of mesoporous carbon, a porous composite carrier including a carrier metal fixed to at least the inner surface of the pores of the inner surface of the pores and the outer surface of the pores of the mesoporous carbon, and electrode catalyst particles supported on the porous composite carrier, and a part or all of the electrode catalyst particles are supported within the pores of the mesoporous carbon via the carrier metal.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an electrode material suitable for electrodes of polymer electrolyte fuel cells, and to an electrode, a membrane electrode assembly, and a polymer electrolyte fuel cell each using the electrode material. [Background technology]

[0002] Fuel cell vehicles (FCVs) that use polymer electrolyte fuel cells (PEFCs) as their power source are already commercially available, and it is expected that their applications will expand and become more widespread in trucks, buses, ships, and other vehicles in the future. PEFCs generally have a structure in which a membrane electrode assembly (MEA), in which a pair of electrodes are arranged on both sides of a solid polymer electrolyte membrane, is sandwiched between separators with gas flow paths. Fuel cell electrodes (particularly PEFC electrodes) generally consist of an electrode catalyst layer made of an electrode material with electrocatalytic activity and a polymer electrolyte, and a gas diffusion layer that combines gas permeability and electronic conductivity.

[0003] Currently, electrode materials in widespread use for PEFCs are those in which electrode catalyst fine particles (typically Pt or Pt alloy fine particles) are dispersed and supported on a carbon-based support. In recent years, electrode materials in which mesoporous carbon is used as the framework of the catalyst support and Pt fine particles are supported within the pores (mesopores) of the mesoporous carbon have attracted attention (e.g., Patent Documents 1 and 2). Mesoporous carbon has excellent electrical conductivity, is easy to diffuse gases, and has a large surface area, so that when it is used as a support for the electrode catalyst of a polymer electrolyte fuel cell, an electrode with excellent power generation performance can be obtained. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent No. 6969996 [Patent Document 2] Patent No. 6931808 Summary of the Invention [Problem to be solved by the invention]

[0005] Incidentally, since the electrolyte membrane of a PEFC is acidic (pH=0-3), the electrode material of the PEFC is used in an acidic atmosphere. In addition, the cell voltage during normal operation is 0.4-1.0V, but it is known that the cell voltage rises to 1.5V during start-up and shutdown. The state of the cathode and anode under such PEFC operating conditions is a region in which the carbon-based material, which is the carrier, decomposes into carbon dioxide (CO2) at the cathode. Therefore, at the cathode, a reaction occurs in which the carbon-based carrier is electrochemically oxidized and decomposed into CO2, resulting in corrosion of the carbon-based carrier (carbon corrosion), which causes aggregation and detachment of Pt particles, which are catalytically active components, and causes a decrease in the performance of the fuel cell. In addition, if the fuel gas is insufficient not only at the cathode but also at the anode at the beginning of operation, a voltage drop or concentration polarization occurs at that part, resulting in a localized potential opposite to normal, and an electrochemical oxidation and decomposition reaction of carbon may occur.

[0006] The electrode materials disclosed in Patent Documents 1 and 2, in which Pt microparticles are supported within the pores (mesopores) of mesoporous carbon, are said to be less susceptible to aggregation of the Pt microparticles. However, because the Pt microparticles are supported in direct contact with the pore walls of the mesoporous carbon, carbon corrosion is unavoidable, and there is a problem in that it is impossible to prevent aggregation and falling off of the Pt particles due to carbon corrosion when generating electricity for a long period of time.

[0007] Under these circumstances, an object of the present invention is to provide an electrode material that provides a fuel cell electrode having excellent electrode performance and durability, and an electrode, a membrane electrode assembly, and a solid polymer electrolyte fuel cell that use the same. [Means for solving the problem]

[0008] As a result of intensive research aimed at solving the above problems, the present inventors found that the following invention meets the above object, and thus completed the present invention.

[0009] That is, the present invention relates to the following inventions. <1> An electrode material which is either electrode material (A) or electrode material (B) below. Electrode material (A): A porous composite support comprising a support skeleton made of mesoporous carbon and a support metal fixed to at least the inner pore surface of the mesoporous carbon pore inner surface and the outer pore surface, and electrode catalyst particles supported on the porous composite support; An electrode material in which a part or all of the electrode catalyst particles are supported within the pores of the mesoporous carbon via the support metal. Electrode material (B): A support skeleton made of mesoporous carbon and an electrode catalyst composite fixed to at least the inner pore surface of the mesoporous carbon, among the inner pore surface and the outer pore surface, The electrode catalyst composite is an electrode material that includes electrode catalyst particles and a support metal, the support metal being present so as to fill the spaces between the electrode catalyst particles. <2> The carrier metal is any metal selected from tantalum (Ta), tungsten (W), niobium (Nb) and tin (Sn), or an alloy containing these metals as a main component. <1> The electrode material according to claim 1. <3> The carrier metal is tantalum (Ta) or a tantalum alloy. <1> or <2> The electrode material according to claim 1. <4> The mesoporous carbon has interconnected pores in which some or all of the pores in the mesopore regions are interconnected with the pores in the adjacent mesopore regions. <1> from <3> 13. The electrode material according to claim 12, <5> The pore size of the mesoporous carbon is 3 nm or more and 40 nm or less. <1> from <4> 13. The electrode material according to claim 12, <6> The electrode catalyst particles are particles made of Pt or an alloy containing Pt. <1> from <5> 13. The electrode material according to claim 12, <7> <1> from <6> 13. An electrode comprising the electrode material according to any one of claims 1 to 12 and a proton-conducting electrolyte material. <8> A membrane electrode assembly having a solid polymer electrolyte membrane, a cathode bonded to one side of the solid polymer electrolyte membrane, and an anode bonded to the other side of the solid polymer electrolyte membrane, wherein either or both of the anode and the cathode are <7> A membrane electrode assembly comprising the electrode according to claim 1. <9> <8> 2. A polymer electrolyte fuel cell comprising the membrane electrode assembly according to claim 1. Effect of the Invention

[0010] According to the present invention, there are provided an electrode material that provides a fuel cell electrode having excellent electrode performance and durability, as well as an electrode, a membrane electrode assembly, and a polymer electrolyte fuel cell that use the same. [Brief description of the drawings]

[0011] [Figure 1] 1(a) is a conceptual schematic diagram of an example of an electrode material of the present invention, (b) is an enlarged schematic diagram of the vicinity of the pores (support metal is dispersed and fixed), and (c) is an enlarged schematic diagram of the vicinity of the pores (support metal is continuously fixed (coated)). [Diagram 2] FIG. 2(a) is a conceptual schematic diagram of another example of the electrode material of the present invention, and FIG. 2(b) is an enlarged schematic diagram of the vicinity of a pore. [Diagram 3] 1 is a schematic cross-sectional view of a membrane electrode assembly of the present invention. [Figure 4] FIG. 1 is a conceptual diagram showing a typical configuration of a polymer electrolyte fuel cell according to the present invention. [Diagram 5] 1 is a flowchart showing a procedure for producing an electrode material (Ta / MC, no electrode catalyst supported) in an experimental example. [Figure 6] 1 is a flowchart of a procedure for producing an electrode material (Pt / Ta / MC) in an experimental example. [Figure 7] 1 shows an FESEM image and a STEM image of the electrode material of Example 1 (electrode catalyst not supported, reduction treatment at 300° C. for 4 hours). [Figure 8] 1 shows an FESEM image and a STEM image of the electrode material of Example 2 (electrode catalyst not supported, reduction treatment at 500° C. for 2 hours). [Figure 9]1 is a STEM image of the electrode material of Example 3 (electrode catalyst not supported, reduction treatment at 600° C. for 2 h). [Figure 10] 1 shows cyclic voltammograms (CV) of the electrode material (Pt / Ta / MC) of Example 2 and the electrode material (Pt / MC) of the comparative example. [Figure 11] FIG. 1 is a diagram showing the electrochemically effective surface area (ECSA) of the electrode material (Pt / Ta / MC) of Example 2 and the electrode material (Pt / MC) of the comparative example. [Figure 12] 1 shows linear sweep voltammograms (LSV, 1600 rpm) of the electrode material (Pt / Ta / MC) of Example 2 and the electrode material (Pt / MC) of the comparative example. [Figure 13] FIG. 1 is a graph showing the mass activity (0.9VRHE) of the electrode material (Pt / Ta / MC) of Example 2 and the electrode material (Pt / MC) of the comparative example. [Figure 14] FIG. 13 is a diagram showing conditions of a start-stop cycle test. [Figure 15] FIG. 1 is a diagram showing the relationship between the number of start-stop cycle tests and the electrochemically effective surface area (ECSA) for the electrode material of Example 2 (Pt / Ta / MC) and the electrode material of the comparative example (Pt / MC) (Example 2: Pt / Ta / MC, Comparative example: Pt / MC). [Figure 16] FIG. 13 is a diagram showing conditions of a load change cycle test. [Figure 17] FIG. 1 is a graph showing the relationship between the number of load change cycle tests and the electrochemically effective surface area (ECSA) for the electrode material (Pt / Ta / MC) of Example 2. [Figure 18] 1 shows the LSV (1600 rpm) of the electrode material (Pt / Ta / MC) of Example 2 before and after the load change cycle test. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The present invention will be described in detail below with reference to examples, but the present invention is not limited to the following examples, and can be modified as desired without departing from the gist of the present invention. In this specification, the word "to" is used as an expression including the numerical values ​​or physical quantities before and after it.

[0013] In this specification, the term "pore" includes, for example, pores having a diameter of 150 nm or less (particularly, pores having a diameter of 100 nm or less). "Mesopore region pores" refers to pores having a diameter of 2 nm to 50 nm. In addition, in this specification, "micropore region pores" refers to pores having a diameter of less than 2 nm, and "macropore region pores" refers to pores having a diameter of more than 50 nm and not more than 150 nm.

[0014] <1. Electrode material> The present invention relates to the following electrode material (A) and electrode material (B). The electrode material (A) may be referred to as the electrode material (first embodiment) of the present invention, and the electrode material (B) may be referred to as the electrode material (second embodiment) of the present invention. These may also be collectively referred to as the "electrode material of the present invention."

[0015] Electrode material (A): A porous composite support comprising a support skeleton made of mesoporous carbon and a support metal fixed to at least the inner pore surface of the inner pore surfaces and the outer pore surfaces of the mesoporous carbon, and electrode catalyst particles supported on the porous composite support, An electrode material in which a part or all of the electrode catalyst particles are supported within the pores of the mesoporous carbon via the support metal.

[0016] Electrode material (B): The support includes a support skeleton made of mesoporous carbon and an electrode catalyst composite fixed to at least the inner pore surface of the mesoporous carbon, The electrode catalyst composite is an electrode material that includes electrode catalyst particles and a support metal, the support metal being present so as to fill the spaces between the electrode catalyst particles.

[0017] In this specification, "fixed" means that the support metal (in the case of electrode catalyst (A)) or the electrode catalyst composite (in the case of electrode catalyst (B)) is fixed to the inner and outer pore surfaces of the mesoporous carbon, which is the support skeleton, to an extent that it does not easily detach (peel off).

[0018] In the electrode material (A), the support metal is fixed so as to cover a part or the whole of the inner surface of the pores in the mesopore region of the mesoporous carbon, and the electrode catalyst particles are supported on the support metal. That is, the electrode catalyst particles are supported in the pores in the mesopore region of the mesoporous carbon via the support metal. Note that in the electrode material (A), the electrode catalyst particles may be supported not only inside the pores in the mesopore region, but also on the pores other than the pores in the mesopore region and on the outer surface via the support metal. The form of the fixed carrier metal may be any of particulate, island, thin film, etc., as long as it does not impair the object of the present invention. "Island" means a state in which several particulate carrier metals are aggregated and separated from each other, and "film" means a state in which the carrier metals are continuously connected to form a thin film.

[0019] In the electrode material (B), an electrode catalyst composite consisting of electrode catalyst particles and a carrier metal is fixed so as to cover a part or the whole of the inner surface of the pores in the mesopore region of the mesoporous carbon. Note that in the electrode material (B), the electrode catalyst composite may be fixed not only to the inside of the pores in the mesopore region, but also to the pores other than the pores in the mesopore region and to the outer surface. The form of the fixed electrode catalyst composite may be any of particulate, island, thin film, etc., as long as it does not impair the object of the present invention. "Island" refers to a state in which several particulate support metals are aggregated and separated from each other, and "film" refers to a state in which the support metals are continuously connected to form a thin film.

[0020] The first embodiment (electrode material (A)) and the second embodiment (electrode material (B)) of the electrode material of the present invention have a common feature in that "mesoporous carbon serves as a support skeleton, and electrode catalyst particles and a support metal are present in the pores of the mesoporous carbon." Furthermore, electrode material (A) has a different characteristic in that "a part or all of the electrode catalyst particles are supported in the pores of the mesoporous carbon via a carrier metal", whereas electrode material (B) has a different characteristic in that "a part or all of the electrode catalyst particles are fixed in the pores of the mesoporous carbon as an electrode catalyst composite".

[0021] The electrode material of the present invention is suitable as an electrode material for use in electrodes for polymer electrolyte fuel cells, but can also be used for other purposes (for example, electrodes for polymer electrolyte water electrolysis).

[0022] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS Preferred embodiments of the present invention will now be described in detail with reference to the drawings. In the following, the electrode material of the present invention will be described assuming its use in an electrode for a polymer electrolyte fuel cell (PEFC).

[0023] <Electrode material (A)> Hereinafter, the electrode material (A), which is a first embodiment of the electrode material of the present invention, will be described. FIG. 1(a) is a schematic diagram showing a typical structure of an electrode material (A) of the present invention, and FIG. 1(b) and FIG. 1(c) are enlarged schematic diagrams of the vicinity of pores.

[0024] As shown in FIG. 1(a), an electrode material 1A according to the present invention is composed of a porous composite support comprising mesoporous carbon 2 as a support skeleton and particulate support metal 3a fixed to the mesoporous carbon 2 (pore inner surface 2a and outer surface 2b), and electrode catalyst particles 3b supported on the support metal 3a.

[0025] The electrode material 1A shown in FIG. 1(a) has the carrier metal 3a and the electrode catalyst particles 3b dispersed and supported thereon also on the outer surface 2b, but the carrier metal 3a and the electrode catalyst particles 3b may be present only on the inner surface 2a of the pores.

[0026] The mesoporous carbon 2 which is the support skeleton of the electrode material 1A (hereinafter, may be referred to as "mesoporous carbon according to the present invention") is a porous carbon having a large number of pores in the mesopore region.

[0027] Porous carbon having pores in the mesopore region (2 to 50 nm) can be used as the mesoporous carbon 2, and preferably has a pore diameter of 3 nm to 40 nm. If the pore diameter is within this range, even if a carrier metal or an electrode catalyst is fixed (supported) on the inner wall of the pore, the diffusion of substances into the pores is not significantly hindered and proceeds smoothly.

[0028] Furthermore, as described below, when preparing an electrode for a fuel cell, the electrode material of the present invention is mixed with a proton-conductive electrolyte material (ionomer). Since the proton-conductive electrolyte material (ionomer) has a size of several tens of nanometers, it is unable to penetrate into mesopores having a small pore diameter. This makes it possible to suppress poisoning of the electrode catalyst particles supported via the support metal in the pores of the mesoporous carbon by the ionomer.

[0029] The mesoporous carbon according to the present invention may contain regions (micropore region, macropores) other than the mesopore region (2 nm to 50 nm) pores, but it is preferable that the proportion of pores in the mesopore region is high.

[0030] The pore structure (pore size, shape, etc.) of mesoporous carbon can be confirmed by observation with an electron microscope, such as a field emission scanning electron microscope (FESEM) or a scanning transmission electron microscope (STEM).

[0031] The pores in the mesopore region of the mesoporous carbon 2 preferably have a three-dimensional network structure, including not only individual pores independent of other pores, but also interconnected pores in which some or all of the pores in the mesopore region are interconnected with the pores in adjacent mesopore regions. The presence of interconnected pores promotes the diffusion of substances inside the pores of the mesoporous carbon.

[0032] The size and shape of the electrode material 1A depend on the size and shape of the mesoporous carbon that is its framework material. The size and shape of the mesoporous carbon are determined so that the electrode material can be in continuous contact when the electrode for the fuel cell is formed, and a space can be formed that allows the diffusion of gases such as hydrogen and oxygen and the discharge of water (steam) in the electrode for the fuel cell to be performed smoothly.

[0033] The mesoporous carbon used in the electrode material of the present invention may be appropriately synthesized or may be a commercially available product, such as the CNovel series (designed mesopore diameter: 5 to 150 nm) manufactured by Toyo Tanso Co., Ltd., which is a mesoporous carbon using MgO as a template.

[0034] (Carrier metal) 1, in the fuel cell electrode material 1A of this embodiment, the support metal 3a is fixed to the inner surface 2a of the pores in the mesopore region of the mesoporous carbon 2. In the fuel cell electrode material 1 of this embodiment, the support metal 3a is also fixed to the outer surface of the mesoporous carbon 2, but the support metal on the outer surface is not necessarily required.

[0035] The optimal amount of the support metal to be adhered varies depending on the physical properties of the support metal, such as particle size (film thickness if it is a thin film) and surface area, and the manufacturing method of the support metal, so the amount is appropriately determined within a range in which a sufficient amount of electrode catalyst particles can be supported.

[0036] The size of the support metal in the pores is determined within a range that does not block the pores of the mesoporous carbon 2 and does not inhibit the transfer of substances such as gas. Although it depends on the pore size of the mesoporous carbon 2, the size of the support metal fixed to the inner surface of the pores is preferably a particle size of 0.5 nm or more and 3 nm or less.

[0037] The outer surface carrier metal 3a may be larger than the carrier metal in the pores because it is not substantially involved in blocking the mesopores, but in order to reduce electrical resistance, it is preferable that the particle size is small within a range in which the electrode catalyst particles 3b can be dispersed and supported. When the outer surface carrier metal is present, its size is preferably 0.5 nm or more and 10 nm or less.

[0038] The "average particle size of the particulate carrier metal" can be obtained by averaging the particle sizes of any 20 particulate carrier metal particles examined from an electron microscope image.

[0039] 1(a) and (b), the support metal 3a is a particulate support metal dispersed and fixed on the mesoporous carbon 2, but is not limited thereto, and the support metal 3a may be fixed to the mesoporous carbon 2. For example, as shown in FIG. 1(c), the particulate support metal 3a may not be dispersed but may be continuously fixed to the surface of the mesoporous carbon 2 (particularly the inner surface of the pores) so as to coat the surface in a thin film.

[0040] The carrier metal constituting the carrier metal 3a may be any metal that has sufficient durability and electronic conductivity under at least one of the anode conditions and cathode conditions of the PEFC. The cathode conditions of a PEFC refer to the conditions at the cathode during normal operation of the PEFC, where the temperature is from room temperature to approximately 150°C and an oxygen-containing gas such as air is supplied (oxidizing atmosphere), while the anode conditions refer to the conditions at the anode during normal operation of the PEFC, where the temperature is from room temperature to approximately 150°C and an oxygen-containing fuel gas such as air is supplied (reducing atmosphere).

[0041] Materials used as the support metal include metal species such as tantalum (Ta), tungsten (W), niobium (Nb), and tin (Sn), and alloys containing these metal species as the main components. Note that when these metals are fixed to the electrode material, the outermost surface of the metal may be oxidized to form an oxide layer, but in the present invention, the metals having an oxide layer on the outermost surface are also considered to be support metals.

[0042] In the carrier metal, "an alloy containing a main component" means "an alloy consisting of a main component metal and other metals, containing 50 mass% or more of the main component metal." In the carrier metal, the "other metals" to be alloyed with the main component metal are not particularly limited, but suitable examples include Co, Ni, Ti, W, Ta, Nb, and Sn (however, these are elements different from the main component metal). One or more of these may be used. Also, an alloy containing the main component metal and other metals in a phase-separated state may be used.

[0043] Suitable examples of the carrier metal include any metal selected from tantalum (Ta), tungsten (W) and niobium (Nb), and alloys containing these metals as a main component, and particularly preferred are tantalum (Ta) or tantalum alloys.

[0044] The amount of the support metal is appropriately determined taking into consideration the type of metal used, the physical properties of the mesoporous carbon (pore distribution, specific surface area, etc.), etc. If the amount of the support metal is too small, the amount of the electrode catalyst supported on it will be small, resulting in insufficient electrode performance, whereas if the amount is too large, it will adhere to the outside of the pores of the mesoporous carbon and agglomerate, which may result in reduced performance. The amount of adhered support metal can be examined by, for example, inductively coupled plasma emission spectrometry (ICP).

[0045] (electrode catalyst particles) The electrode catalyst particles 3b are dispersed and supported on the carrier metal 3a. The ratio of the electrode catalyst particles supported on the carrier metal can be evaluated by selecting any electrode catalyst particles (100 or more) observed under an electron microscope from the fuel cell electrode material to be evaluated, and counting the number of particles supported on the carrier metal and the number of particles supported on the mesoporous carbon.

[0046] The electrode catalyst particles 3b may be either a precious metal catalyst or a non-precious metal catalyst as long as it has electrochemical catalytic activity for the reduction of oxygen (and the oxidation of hydrogen), but is preferably selected from precious metals such as Pt, Ru, Ir, Pd, Rh, Os, Au, Ag, and alloys containing these precious metals. The term "alloy containing a precious metal" includes "alloys consisting of only the above-mentioned precious metals" and "alloys consisting of the above-mentioned precious metals and other metals and containing 10 mass % or more of the above-mentioned precious metals". The "other metals" to be alloyed with the precious metal are not particularly limited, but suitable examples include Co and Ni, and one or more of these may be used. Two or more of the above-mentioned precious metals and alloys containing the precious metals in a phase-separated state may also be used. In the present specification, the above-mentioned precious metals and alloys containing these precious metals may be referred to as "electrode catalyst metals" hereinafter.

[0047] Among the electrode catalyst metals, Pt and alloys containing Pt (Pt alloys) are particularly suitable for use because they have high electrochemical catalytic activity for the reduction of oxygen (and the oxidation of hydrogen) in the temperature range around 80°C, which is the operating temperature of solid polymer electrolyte fuel cells. The metal species other than Pt in the Pt alloy is not particularly limited as long as it can form an alloy, but is preferably cobalt (Co).

[0048] The shape of the electrode catalyst particles 3b is not particularly limited, and may be the same as that of known electrode catalyst particles. Specific shapes include a sphere, an ellipse, a polyhedron, a core-shell structure, etc. The structure of the electrode catalyst particles 3b is not limited to a crystal, and may be amorphous or a mixture of a crystal and an amorphous structure.

[0049] The smaller the size of the electrode catalyst particles 3b, the greater the effective surface area for the electrochemical reaction to proceed, and therefore the higher the electrochemical catalytic activity tends to be. However, if the size is too small, the electrochemical reaction activity decreases. Therefore, the size of the electrode catalyst particles 3b is preferably 0.5 to 4 nm as the average particle size.

[0050] In the present invention, the "average particle size of electrode catalyst particles" can be obtained by averaging the particle sizes of electrode catalyst particles (20 particles) examined from an electron microscope image. When calculating the average particle size from an electron microscope image, if the shape of the fine particles is other than spherical, the length in the direction showing the maximum length of the particle is taken as the particle size.

[0051] The amount of electrode catalyst particles supported is appropriately determined taking into consideration the type of catalyst, the size (thickness) of the carrier metal, and other conditions. If the amount of catalyst supported is too small, the electrode performance will be insufficient, and if it is too large, the electrode catalyst particles may aggregate and performance may decrease. The amount of electrode catalyst particles supported can be examined, for example, by inductively coupled plasma emission spectrometry (ICP).

[0052] The method for producing the above-mentioned electrode material (A) is not particularly limited, and a suitable method may be selected depending on the types of mesoporous carbon, support metal, and electrode catalyst particles constituting the electrode material (A). Usually, a method is employed in which the support metal is supported on the mesoporous carbon, and then the electrode catalyst particles are supported on the support metal. It should be noted that the method employed in the examples described below makes it possible to fix a support metal of sub-nano order inside the pores of the mesoporous carbon that constitutes the support skeleton.

[0053] In addition, a known metal supporting method can be adopted as a method for supporting the electrode catalyst precursor or electrode catalyst particles on the carrier metal. A suitable example is a method (noble metal acetylacetonate method) in which a noble metal acetylacetonate is used as the electrode catalyst precursor adopted in the examples. In the acetylacetonate method, mesoporous carbon supporting the carrier metal is dispersed in a solution in which a noble metal acetylacetonate is dissolved in a suitable solvent such as dichloromethane, and the solution is stirred and the solvent is distilled off, whereby electrode catalyst particles with a uniform nano-sized particle size distribution can be supported on the carrier metal with good dispersibility.

[0054] <Electrode material (B)> Hereinafter, the electrode material (B) which is the second embodiment of the electrode material of the present invention will be described. In the following description, the contents overlapping with the electrode material (A) will be omitted as appropriate.

[0055] FIG. 2(a) is a conceptual schematic diagram showing a representative structure of electrode material (B) (second embodiment) of the present invention, and FIG. 2(b) is an enlarged schematic diagram of the vicinity of a pore. The electrode material (second embodiment) of the present invention is characterized in that the electrode catalyst particles fixed to the mesoporous carbon form an electrode catalyst structure together with the support metal.

[0056] As shown in Fig. 2(a), an electrode material 1B (second embodiment) according to the present invention is composed of mesoporous carbon 2, which is a support skeleton, and an electrode catalyst composite 3 fixed to the mesoporous carbon (pore inner surface 2a and pore inner and outer surfaces 2b). Note that, although the electrode material 1B shown in Fig. 2(a) has the electrode catalyst composite 3 also on the outer surface 2b, the electrode catalyst composite 3 may be present only on the pore inner surface 2a.

[0057] That is, in the electrode material 1B, the electrode catalyst composite 3 is supported on a part or the entirety of the inner pore surfaces of the mesopore regions of the mesoporous carbon 2.

[0058] In the electrode material 1B, the electrode catalyst composite 3 may be supported not only inside the pores in the mesopore region, but also on the outer surface and in pores other than the pores in the mesopore region.

[0059] In the electrode material (B), the mesoporous carbon 2 has a function as a support for fixing (supporting) the electrode catalyst composite, a role for improving the electronic conductivity when the electrode is formed, and a role for serving as the skeleton of the electrode. The same mesoporous carbon as that in the electrode material (A) can be used as the mesoporous carbon, and therefore a description thereof will be omitted.

[0060] In the electrode material (B), the electrode catalyst composite 3 includes a carrier metal 3a and electrode catalyst particles 3b, and is characterized in that the carrier metal 3a is present so as to fill the gaps between the electrode catalyst particles 3b. The electrode catalyst composite 3 can suppress the electrode catalyst particles 3b from agglomerating and becoming enlarged because the carrier metal 3a is present so as to fill the gaps between the electrode catalyst particles 3b. Furthermore, the electrode catalyst composite 3 is also fixed to the mesoporous carbon surface (particularly the inner pore surface), so that the electrode catalyst composite itself can be suppressed from agglomerating.

[0061] In Fig. 2, the support metal present between the electrode catalyst particles is in the form of particles, but the form of the support metal is not limited to particles and may be amorphous as long as it is present between the electrode catalyst particles. Also, the support metal may be crystalline or amorphous, but it is preferable that a part of it is crystalline (i.e., a mixture of crystalline and amorphous), and it is more preferable that the entirety is crystalline.

[0062] In the electrode material (B), since the mesoporous carbon serves as the skeleton of the electrode, the particle size of the electrode catalyst composite 3 can be made small.

[0063] The "size of the electrode catalyst composite" can be obtained by averaging the sizes of any electrode catalyst composites (20 pieces) examined from electron microscope images. If the shape of the electrode catalyst composite is not spherical, the length in the direction showing the maximum length is taken as the size of the electrode catalyst composite.

[0064] In the electrode material (B), a part or the whole of the electrode catalyst composite may be present in the pores of the mesoporous carbon. In this case, the size of the electrode catalyst composite must be smaller than the diameter of the pores of the mesoporous carbon, and is 2 to 30 nm, which corresponds to the pore diameter of the mesoporous carbon (e.g., 3 to 40 nm).

[0065] The proportion of electrode catalyst composites within the pores of the mesoporous carbon is preferably 50% or more, more preferably 80% or more, and even more preferably 90% or more (including 100%), when the total number of electrode catalyst composites (the sum of electrode catalyst composites outside and inside the pores) is taken as 100%. The number of electrocatalyst complexes in the pores of mesoporous carbon can be confirmed using high-angle-scattering dark-field scanning transmission electron microscopy (HAADF-STEM).

[0066] The size of the electrode catalyst composite in the pores is determined within a range that does not block the pores of the mesoporous carbon and does not inhibit the transfer of substances such as gases. Although it depends on the pore size of the mesoporous carbon, the size of the electrode catalyst composite adhered to the inner surface of the pores is preferably a particle size of 0.5 nm or more and 15 nm or less.

[0067] The electrode catalyst composite on the outer surface is not substantially involved in blocking the mesopores, and may be larger than the electrode catalyst composite inside the pores, but preferably has an average particle size of 10 to 500 nm. The "average particle size of the electrode catalyst composite" can be obtained by averaging the particle sizes of any electrode catalyst composites (20 particles) examined from an electron microscope image.

[0068] The amount of the electrode catalyst composite supported is appropriately determined within a range in which a sufficient amount of the electrode catalyst metal is contained as an electrode. Since the activity of the electrode catalyst metal depends on the type, crystallinity, particle size, etc. of the electrode catalyst metal and the type, crystallinity, particle size, etc. of the support metal to be composited, the amount of the electrode catalyst composite supported is determined taking this into consideration.

[0069] The support metal and electrode catalyst metal constituting the electrode catalyst composite of the electrode material (B) will be described in detail below.

[0070] The support metal constituting the electrode catalyst composite is the same as the support metal explained in the above-mentioned electrode material (A), so a detailed explanation is omitted and only a brief explanation is given below.

[0071] The support metal constituting the electrode catalyst composite has sufficient durability and electronic conductivity under PEFC cathode conditions and / or PEFC anode conditions. The form of the support metal is arbitrary as long as it does not impair the object of the present invention, and examples of the form include particulate, island, film, etc. Furthermore, the support metal is not limited to being crystalline, and may be amorphous or a mixture of crystalline and amorphous, but in order to enhance better electronic conductivity, the support metal is preferably crystalline.

[0072] Materials used as the support metal include metal species such as tantalum (Ta), tungsten (W), niobium (Nb), and tin (Sn), and alloys containing these metal species as the main components. Note that when these metals are fixed to the electrode material, the outermost surface of the metal may be oxidized to form an oxide layer, but in the present invention, the metals having an oxide layer on the outermost surface are also considered to be support metals.

[0073] Suitable examples of the carrier metal include any metal selected from tantalum (Ta), tungsten (W) and niobium (Nb), and alloys containing these metals as a main component, and particularly preferred are tantalum (Ta) or tantalum alloys.

[0074] As described above, in the electrode catalyst composite of the present invention, the support metal is present so as to fill the spaces between the electrode catalyst particles, thereby inhibiting the aggregation of the electrode catalyst particles, and the support metal may be contained in a form that can achieve this purpose. The proportion of the support metal in the electrode catalyst composite is appropriately determined depending on the type, size and crystallinity of the support metal, as well as the type, amount and size of the electrode catalyst metal to be composited.

[0075] In the electrode material of the present invention, the carrier metal fills the gaps between the electrode catalyst particles in the electrode catalyst composite, and the carrier metal can be made small, so that the electrical resistance caused by the carrier metal can be reduced. Therefore, the carrier metal may be not only crystalline, but also amorphous. However, in order to further reduce the electrical resistance, it is preferable that at least a part of the carrier metal is crystalline, and it is preferable that the entire carrier metal is crystalline.

[0076] The amount of the support metal is appropriately determined taking into consideration the type of support metal, the type and size of the electrode catalyst particles constituting the electrode catalyst composite, the physical properties of the mesoporous carbon (pore distribution, specific surface area, etc.), etc. If the amount of the support metal is too small, it is not possible to suppress the aggregation of the electrode catalyst in the electrode catalyst composite, and if the amount is too large, a large amount of the support metal adheres to the outside of the pores of the mesoporous carbon, and may aggregate and deteriorate the performance. The amount of adhered support metal can be examined, for example, by inductively coupled plasma emission spectrometry (ICP).

[0077] The electrode catalyst particles constituting the electrode catalyst composite are the same as the electrode catalyst particles explained in the above-mentioned electrode material (A), so a detailed explanation is omitted and only a brief explanation is given below.

[0078] The electrode catalyst particles may be any particles having electrochemical catalytic activity for the reduction of oxygen (and the oxidation of hydrogen), but are preferably electrode catalyst metals selected from precious metals such as Pt, Ru, Ir, Pd, Rh, Os, Au, Ag, etc., and alloys containing these precious metals.

[0079] Among the electrode catalyst metals, Pt and alloys containing Pt (Pt alloys) are particularly suitable for use because they have high electrochemical catalytic activity for the reduction of oxygen (and the oxidation of hydrogen) in the temperature range around 80°C, which is the operating temperature of solid polymer electrolyte fuel cells. The metal species other than Pt in the Pt alloy is not particularly limited as long as it can form an alloy, but is preferably cobalt (Co).

[0080] Furthermore, the electrode catalyst metal is preferably crystalline, but may be a mixture of crystalline and amorphous materials.

[0081] That is, one of the suitable aspects of the electrocatalyst metal in the electrocatalyst (B) is that the electrocatalyst metal is particles made of a noble metal (preferably Pt or an alloy containing Pt) having an average particle size of 1 to 10 nm.

[0082] The amount of the electrocatalyst metal is determined in consideration of the desired electrocatalytic activity and the type and amount of the support metal to be composited. The amount of the electrocatalyst metal supported can be determined, for example, by inductively coupled plasma emission spectrometry (ICP).

[0083] From the viewpoint of electrode catalytic activity, when the amount is preferably 0.1 to 60 mass %, and more preferably 0.5 to 30 mass %, relative to the total weight of the electrode material, excellent catalytic activity per unit mass can be obtained, and a desired electrode reaction activity according to the amount carried can be obtained.

[0084] The method for producing the electrode material (B) is not particularly limited, and a suitable method may be selected depending on the types of mesoporous carbon, carrier metal, and electrode catalyst metal that constitute the electrode material. An example of a method for producing the electrode material (B) includes a production method including the steps of: (1) dissolving an acetylacetonate compound of an electrode catalyst metal precursor and an acetylacetonate compound of a support metal precursor in a dispersion liquid obtained by dispersing mesoporous carbon in an aqueous organic solvent, stirring the mixture, and distilling off the solvent to obtain a support skeleton carrying the electrode catalyst metal precursor and the support metal precursor; and (2) heat-treating the support skeleton carrying the electrode catalyst metal precursor and the support metal precursor obtained in (1) in an inert gas atmosphere to form an electrode catalyst composite.

[0085] <2. Electrode> The electrode of the present invention includes the above-mentioned electrode material of the present invention and a proton-conductive electrolyte material. In the electrode of the present invention, the electrode materials of the present invention are in contact with each other to form a conductive path.

[0086] A fuel cell electrode formed using the electrode material of the present invention will be described below. Specifically, the case where the above-mentioned electrode material is used as an electrode in a PEFC will be described.

[0087] This fuel cell electrode may be composed of only the above-mentioned electrode material, but usually contains a proton-conductive electrolyte material used in the electrolyte of the fuel cell (hereinafter, sometimes referred to as "proton-conductive electrolyte material" or simply "electrolyte material"). The electrolyte material contained in the fuel cell electrode together with the electrode material may be the same as or different from the electrolyte material used in the electrolyte membrane for the fuel cell. From the viewpoint of improving the adhesion between the fuel cell electrode and the electrolyte membrane, it is preferable to use the same one.

[0088] Proton-conductive electrolyte materials are used as electrolyte materials for the electrodes and electrolyte membranes of PEFCs. These proton-conductive electrolyte materials are roughly divided into fluorine-based electrolyte materials that contain fluorine atoms in all or part of the polymer backbone, and hydrocarbon-based electrolyte materials that do not contain fluorine atoms in the polymer backbone, and both of these can be used as electrolyte materials.

[0089] Specific preferred examples of fluorine-based electrolyte materials include Nafion (registered trademark, manufactured by DuPont), Aciplex (registered trademark, manufactured by Asahi Kasei Corporation), and Flemion (registered trademark, manufactured by Asahi Glass Co., Ltd.).

[0090] Specific examples of suitable hydrocarbon electrolyte materials include polymers such as polysulfonic acid, polystyrene sulfonic acid, polyaryl ether ketone sulfonic acid, polyphenyl sulfonic acid, polybenzimidazole sulfonic acid, polybenzimidazole phosphonic acid, and polyimide sulfonic acid, as well as polymers having side chains such as alkyl groups.

[0091] The mass ratio of the electrode material to the electrolyte material mixed with the electrode material may be appropriately determined so as to provide good proton conductivity in the electrode formed using these materials and to smoothly diffuse gas and discharge water vapor in the electrode. However, if the amount of electrolyte material mixed with the electrode material is too large, the proton conductivity is improved but the gas diffusibility is reduced. Conversely, if the amount of electrolyte material mixed is too small, the gas diffusibility is improved but the proton conductivity is reduced. Therefore, the mass ratio of the electrolyte material to the electrode material is preferably in the range of 10 to 50 mass%. If this mass ratio is less than 10 mass%, the continuity of the material having proton conductivity is poor, and sufficient proton conductivity as an electrode for a fuel cell cannot be ensured. Conversely, if it is more than 50 mass%, the continuity of the electrode material is poor, and it may not be possible to have sufficient electronic conductivity as an electrode for a fuel cell. Furthermore, the diffusibility of gas (oxygen, hydrogen, water vapor) inside the electrode may be reduced.

[0092] The fuel cell electrode of the present invention may contain components other than the above-mentioned electrode material and proton conductive material, provided that the object of the present invention is not impaired. For example, the electrode material may contain a conductive material other than the mesoporous carbon (hereinafter, referred to as "other conductive material") contained in the electrode material. By containing the other conductive material, the conductive paths connecting the electrode materials are increased, and the conductivity of the electrode as a whole may be improved.

[0093] As the other conductive material, a known conductive material used in a fuel cell electrode can be used. Typical conductive materials are carbon-based conductive materials, such as particulate carbon (including carbon particles linked in a chain) such as carbon black and activated carbon, and fibrous carbon such as carbon fiber and carbon nanotube (CNT). Unsupported mesoporous carbon can also be used as the other conductive material.

[0094] Although the electrode for a PEFC has been described as an electrode for a fuel cell including the electrode material of the present invention, the electrode material can be used as an electrode for various fuel cells other than PEFC, such as alkaline fuel cells, phosphoric acid fuel cells, etc. The electrode material can also be suitably used as an electrode for a water electrolysis device using a polymer electrolyte membrane similar to that of a PEFC. The electrode for a fuel cell containing the electrode material of the present invention has excellent electrochemical catalytic activity for oxygen reduction and hydrogen oxidation, and can be used as a cathode and an anode. In particular, the electrode has excellent electrochemical catalytic activity for oxygen reduction, and electrochemical oxidative decomposition of the conductive material, which is the carrier, does not occur under the operating conditions of the fuel cell, and therefore can be suitably used as a cathode.

[0095] The fuel cell electrode of the present invention can be used as an electrode in various fuel cells other than PEFC, such as alkaline fuel cells and phosphoric acid fuel cells, and can also be suitably used as an electrode for water electrolysis devices using a solid polymer electrolyte membrane similar to that of PEFC.

[0096] <3. Membrane electrode assembly (MEA)> The membrane electrode assembly of the present invention is a membrane electrode assembly having a solid polymer electrolyte membrane, a cathode bonded to one side of the solid polymer electrolyte membrane, and an anode bonded to the other side of the solid polymer electrolyte membrane, wherein either or both of the cathode and the anode are the above-mentioned electrodes of the present invention.

[0097] As a preferred embodiment of the present invention, a membrane electrode assembly using a fuel cell electrode containing the electrode material of the present invention as a cathode will be described. Fig. 3 is a schematic diagram showing a cross-sectional structure of a membrane electrode assembly according to an embodiment of the present invention. As shown in Fig. 3, a membrane electrode assembly 10 has a structure in which a cathode 4 and an anode 5 are disposed facing a solid polymer electrolyte membrane 6.

[0098] The cathode 4 is composed of an electrode catalyst layer 4a and a gas diffusion layer 4b.

[0099] As the gas diffusion layer 4b, a conventionally known gas diffusion layer can be used. For example, a conductive carbon-based sheet-like member having a pore size distribution of about 100 nm to 90 μm, which has been conventionally used as a gas diffusion layer for PEFC, can be used. Preferably, carbon paper, carbon cloth, carbon nonwoven fabric, etc., which have been subjected to a water-repellent treatment can be used. Also, a sheet-like member other than a carbon-based material such as stainless steel can be used. The thickness of such a gas diffusion layer 4b is not particularly limited, but is usually about 50 μm to 1 mm. Also, the gas diffusion layer 4b may have a microporous layer on one side thereof, which is made of an aggregate of carbon fine particles having an average particle size of about 10 to 100 nm and a water-repellent material.

[0100] The anode 5 is composed of an electrode catalyst layer 5a and a gas diffusion layer 5b. As the anode 5, in addition to the fuel cell electrode of the present invention, other known anodes can be used in the same manner. For example, an electrode in which an electrode catalyst layer 5a is formed on a gas diffusion layer 5b by applying and drying a dispersion of an electrode material carrying precious metal particles as a catalyst and an electrolyte material of a fuel cell on the surface of a conductive support made of a carbon-based material such as graphite, carbon black, activated carbon, carbon nanotube, or glassy carbon. The gas diffusion layer 5b of the anode 5 can be the same as the gas diffusion layer 4b described for the cathode 4.

[0101] Any known electrolyte membrane for PEFC may be used as the solid polymer electrolyte membrane 6 so long as it has proton conductivity, chemical stability, and thermal stability. Although the thickness is exaggerated in FIG. 3, the thickness of the solid polymer electrolyte membrane 6 is usually about 0.007 to 0.05 mm in order to reduce electrical resistance.

[0102] Examples of electrolyte materials constituting the solid polymer electrolyte membrane 6 include fluorine-based electrolyte materials and hydrocarbon-based electrolyte materials. In particular, electrolyte membranes formed from fluorine-based electrolyte materials are preferred because they have excellent heat resistance, chemical stability, etc. Specific examples of suitable materials include Nafion (registered trademark, manufactured by DuPont), Aciplex (registered trademark, manufactured by Asahi Kasei Corporation), and Flemion (registered trademark, manufactured by Asahi Glass Co., Ltd.).

[0103] Although the embodiments of the MEA of the present invention have been described above with reference to the drawings, these are merely examples of the present invention, and various configurations other than those described above can also be adopted.

[0104] <4. Polymer electrolyte fuel cell> The polymer electrolyte fuel cell (single cell) of the present invention comprises the membrane electrode assembly of the present invention, and generally has a structure in which the membrane electrode assembly is sandwiched between separators having gas flow paths formed therein.

[0105] 4 is a conceptual diagram showing a typical configuration of a polymer electrolyte fuel cell according to the present invention. As shown in FIG. 4, hydrogen is supplied to the anode 5 in a polymer electrolyte fuel cell 20, and (reaction 1) 2H2→ 4H + +4e - The protons (H + ) is supplied to the cathode 4 through the solid polymer electrolyte membrane 6, and the generated electrons are supplied to the cathode through the external circuit 21, resulting in (Reaction 2) O2 + 4H + +4e - →2H2O reacts with oxygen to produce water. A potential difference is generated between the two electrodes by the electrochemical reaction between the anode and the cathode. In the polymer electrolyte fuel cell of the present invention, the components other than the membrane electrode assembly of the present invention are similar to those of known polymer electrolyte fuel cells, and therefore detailed description thereof will be omitted. In practice, a fuel cell stack is formed by stacking the solid polymer electrolyte fuel cell (single cell) of the present invention in a number appropriate for the power generation performance, and the stack is used by assembling other associated devices such as a gas supply device and a cooling device. EXAMPLES

[0106] Examples are given below to describe the present invention more specifically, but the present invention is not limited thereto.

[0107] 1. Preparation of Electrode Material The electrode materials of the following examples and comparative examples were manufactured.

[0108] The porous carbon, noble metal precursor compound, and electronic conductive oxide used were as follows. <Porous Carbon> As the porous carbon, the following mesoporous carbon (MC) (manufactured by Toyo Tanso Co., Ltd., "Porous Carbon C Novel MJ(4)010 (grade name)") was used. Designed pore diameter: 10 nm Specific surface area: 1100 m 2 / g Total pore volume: 2.0 mL / g Micropore volume: 0.4 mL / g Particle size: 100 mesh pass (used after pulverization) <Ta Raw Material Compound> As the Ta raw material compound, tantalum ethoxide (Ta(OC2H5)4, High Purity Chemical Research Institute Co., Ltd.) was used. <Noble Metal Precursor Compound> As the noble metal precursor compound, Pt acetylacetonate (Pt(C5H7O2)2, Platinum(II) acetylacetonate, 97%, Sigma Aldrich) was used. In some cases, Pt acetylacetonate may be hereinafter referred to as Pt precursor (Pt(acac)2).

[0109] <Examples 1 to 3> As shown in the flowchart of FIG. 5, the electrode materials (electrode catalysts not supported) of the examples were prepared by the steam hydrolysis method. First, 50 mg of the above mesoporous carbon (MC), which is the support skeleton, was pulverized in a ball mill to a particle size of about 1 μm, and then dispersed in an organic solvent (a mixture of acetylacetone and toluene in a volume ratio of 2:1) to obtain a dispersion containing MC. Next, a tantalum ethoxide reagent was dissolved in an organic solvent (ethanol) to prepare a metal ethoxide solution in which Ta was 35 wt%. This metal ethoxide solution was added to the dispersion containing MC, and the total amount of solvent was adjusted to 50 mL. The pressure was reduced while ultrasonic stirring was performed, and the organic solvent was evaporated to obtain a dry powder in which the metal ethoxide reagent was uniformly adsorbed on the MC surface (inner and outer surfaces of the pores). The obtained dry powder was pulverized and then held for 1 hour in a 30°C water vapor nitrogen atmosphere (3% humidified N2 atmosphere) to allow steam hydrolysis of the metal ethoxide reagent to proceed, and then heated to 400°C in a nitrogen atmosphere and held for 2 hours, and further heated to 800°C in a nitrogen atmosphere and held for 30 minutes. Thereafter, the mixture was held for a predetermined time at a predetermined temperature in a hydrogen atmosphere for reduction treatment to produce the electrode materials (Ta / MC, no electrode catalyst supported) of Examples 1 to 3. Table 1 shows the conditions in the hydrogen atmosphere during the preparation of the electrode materials (Ta / MC) of Examples 1 to 3.

[0110] [Table 1]

[0111] Next, as shown in the flow chart of Fig. 6, Pt catalyst particles, which are electrode catalyst particles, were supported on the electrode material (electrode catalyst unsupported) of Example 2 by the platinum acetylacetonate method. The amount of Pt precursor (Pt(acac)2) was adjusted so that Pt was 32 wt%. The electrode material of Example 2 (electrode catalyst not supported) consisting of tantalum-supported MC and Pt precursor were added to the eggplant flask, and acetone was further added to dissolve. Next, while cooling the eggplant flask on ice, the mixture was stirred with an ultrasonic stirrer until all the solvent was evaporated to obtain a dry powder. Next, the obtained dry powder was subjected to reduction treatment in an N2 atmosphere at 210°C for 3 hours and at 240°C for 3 hours to obtain the electrode material of Example 2 (Pt / Ta / MC).

[0112] <Comparative Example> As a comparative example, a comparative electrode material (Pt / MC) was obtained in the same manner as in Example 1, except that the metal ethoxide solution was not used.

[0113] <Reference example> As a reference example, a commercially available platinum-supported carbon black catalyst (Pt / C, (Tanaka Kikinzoku Kogyo Co., Ltd., TEC10E50E) was used.

[0114] 2. Physical property evaluation (microstructure observation) (1) Electrode material (without electrode catalyst) Fig. 7 shows FESEM and STEM images of the electrode material (electrode catalyst not supported) of Example 1, Fig. 8 shows FESEM and STEM images of the electrode material (electrode catalyst not supported) of Example 2, and Fig. 9 shows a STEM image of the electrode material (electrode catalyst not supported) of Example 3. Note that the residual oxygen values ​​below are values ​​measured by energy dispersive X-ray spectroscopy (EDS). As shown in Figures 7 to 9, it was confirmed that Ta particles were uniformly supported in all of the electrode materials (electrode catalyst not supported) of Examples 1 to 3. In addition, the residual oxygen was 8 to 10% in Example 1 (hydrogen atmosphere, 300°C, 4 hours), and the residual oxygen was 4 to 5% in Example 2 (hydrogen atmosphere, 500°C, 2 hours) and Example 3 (hydrogen atmosphere, 600°C, 2 hours). Therefore, it was determined that the reduction of the Ta precursor to Ta was more advanced by heat treatment at 500°C or higher in a hydrogen atmosphere. In addition, it was determined from Figure 9 that in Example 3 (hydrogen atmosphere, 600°C, 2 hours), there were portions of Ta monoatoms and portions of about 10 atomic layers in the pores.

[0115] 3. Electrochemical evaluation (half cell) 3-1. Evaluation of cyclic voltammetry (CV) The electrode materials of Example 2 (Pt / Ta / MC) and Reference Example (Pt / C) were evaluated by cyclic voltammetry (CV). The electrochemical surface area (ECSA) was calculated from the amount of hydrogen adsorption determined by CV. The ECSA corresponds to the effective surface area of ​​Pt contained in the electrode material.

[0116] The fuel cell electrodes for evaluation were prepared in the following manner. First, a mixed solution of 19 mL of ultrapure water and 6 mL of 2-propanol was added to a sample bottle containing the electrode material powder, followed by the addition of 100 μL of 5% Nafion dispersion. The sample bottle was then immersed in ice water and ultrasonically stirred for 30 minutes to obtain an electrode material dispersion. The amount of electrode material powder was determined based on the amount of Pt per unit area on the electrode when 10 μL of the electrode material dispersion was dropped onto the electrode. -Pt / cm 2 10 μL of the prepared electrode material dispersion was dropped onto the Au disk electrode using a micropipette and placed in an incubator and dried at 60° C. for about 15 minutes to form a Nafion membrane and fix the electrode material onto the Au electrode, thereby obtaining a fuel cell electrode (working electrode) for evaluation.

[0117] The CV measurement conditions are as follows. Assuming that one atom of H is adsorbed per one atom of Pt, the CV is 210 μC / cm 2 This results in an electrical charge of Measurement: Three-electrode cell (working electrode: fuel cell electrode for evaluation, counter electrode: Pt, reference electrode: Ag / AgCl) Electrolyte: 0.1M HClO4 (pH: approx. 1) Measurement potential range: 0.05 to 1.2 V (based on the reversible hydrogen electrode) Scan speed: 50 mV / s Amount of hydrogen adsorption: Calculated from the peak area showing hydrogen adsorption at 0.05 to 0.4 V Electrochemical surface area (ECSA): Calculated using the following formula ECSA=(hydrogen adsorption amount)[μC] / 210[μC / cm 2 ]

[0118] Fig. 10 shows cyclic voltammograms of the electrode materials of Example 2 and Reference Example. As shown in Fig. 10, in the electrode using the electrode material of Example 2 (Pt / Ta / MC), a peak (0.05 to 0.4 V) due to the adsorption and desorption of hydrogen originating from Pt was observed, and it was confirmed that the electrode functions as an electrode for a fuel cell. Furthermore, the electrode material of Example 2 (Pt / Ta / MC) was comparable to the electrode material of the Reference Example (Pt / C, TEC10E50E), and as shown in FIG. 11, it was confirmed that the electrochemical surface area (ECSA) was equivalent (ECSA Example 2: 78.5 m 2 / g, reference example: 73.8m 2 / g).

[0119] 3-2. Evaluation of ORR activity The electrode materials of Example 2 and Reference Example were evaluated for ORR activity. ORR activity was measured by linear sweep voltammetry (LSV) using the rotating disk electrode (RDE) method, and the activation-dominant current (i k ) was used as an index. Mass activity = i k / mass of Pt on electrode Activation dominant current (i k ) is the current-potential curve obtained by rotating electrode measurement at any potential i -1 and ω -1 / 2 A Koutecky-Levich plot was created by plotting the above-mentioned line, and the intercept was determined by extrapolating the obtained line. The specific procedure is as follows: First, O2 was bubbled at 50 mL / min for 30 min, and then 0.2 V RHE 1.20 V at 10 mV / s in the positive direction RHE The potential was scanned up to 1000 V, and the measurements were performed. During the measurements, O2 was constantly purged at 50 mL / min.RHE is the potential relative to the reversible hydrogen electrode (RHE).

[0120] FIG. 12 shows linear sweep voltammograms (1600 rpm) of the electrode materials of Example 2 and Reference Example, and FIG. 13 shows the ORR measurement results of the electrode material of Example 2 at 0.9 V RHE Mass activity at this time was 179.2A / g Pt Although this was not as good as that of the reference example, it showed a relatively high initial activity. It was determined that the high activity was due to the conductive path secured by the conductivity of the Ta metal.

[0121] 3-3. Start-stop cycle test A start-stop cycle test was conducted on the electrode materials of Example 2 and Comparative Example by the method recommended by the Fuel Cell Commercialization Promotion Council of Japan (FCCJ) (Proposal of the Goals, Research and Development Issues, and Evaluation Methods of Polymer Electrolyte Fuel Cells, published in January 2011). The start-stop cycle test is a cycle test that promotes carbon corrosion, and specifically, the start-stop cycle test was conducted at 1.0 to 1.5 V as shown in FIG. RHE A square wave of this voltage is applied for 2 seconds per cycle, and the deterioration behavior of the electrode catalyst after the cycle test is evaluated as a change in ECSA.

[0122] FIG. 15 shows the change in ECSA of the electrodes using the electrode materials of Example 2 and the comparative example in a start-stop cycle test (up to 20,000 cycles). As shown in FIG. 15, the ECSA of Example 2 (Pt / Ta / MC) was slightly smaller than that of the Comparative Example (Pt / MC) up to 5000 cycles, but after 5000 cycles, the relationship was reversed and Example 2 became larger than the Comparative Example.

[0123] 3-4. Load change cycle test A load change cycle durability test was carried out on the electrode materials of Example 2 and Comparative Example. The load change cycle test was carried out by applying a potential cycle simulating a load change according to the method recommended by the Fuel Cell Commercialization Promotion Council of Japan (FCCJ) (Proposal of Objectives, Research and Development Issues and Evaluation Methods for Polymer Electrolyte Fuel Cells, published in January 2011). The load change cycle shown in FIG. 16 is a cycle that promotes deterioration accompanied by dissolution and redeposition of the catalyst itself, and was carried out at a potential change of 0.6 to 1.0 V. RHE The experiment was carried out by applying a rectangular wave of 1000 V for 6 seconds, with 3 seconds per cycle, and measuring the changes in ECSA and LSV before and after the load change cycle test.

[0124] The ECSA retention rate after the load change cycle test (400,000 cycles) is shown in Figure 17. The ECSA retention rate after the load change cycle test (400,000 cycles) was 43% for the electrode material (Pt / Ta / MC) of Example 2. The LSV change of the electrode material of Example 2 before and after the load change cycle test (400,000 cycles) is shown in Figure 18. It can be seen that the negative shift of the LSV curve is suppressed to some extent, and activity is maintained even after 400,000 cycles. [Industrial Applicability]

[0125] The electrode material of the present invention can provide a fuel cell electrode having excellent electrocatalytic activity, electronic conductivity, gas diffusion, and excellent durability, and is promising as an electrode component of solid polymer fuel cells used in the automobile, electric power, gas, and home appliance industries. In particular, it is expected to be used for fuel cell vehicles (passenger cars and commercial vehicles) that are subject to large load fluctuations. [Explanation of symbols]

[0126] 1A,1B Electrode material 2. Mesoporous carbon 2a Pore inner surface 2b Outer surface 3 Electrocatalyst composite 3a Support metal 3b Electrocatalyst particles 4. Fuel cell electrodes (cathode) 4a Electrode catalyst layer (cathode) 4b Gas diffusion layer 5. Fuel cell electrodes (anodes) 5a Electrode catalyst layer (anode) 5b Gas diffusion layer 6 Solid polymer electrolyte membrane 10 Membrane electrode assembly (MEA) 20 Polymer electrolyte fuel cell 21 External circuit P Pore (mesopore)

Claims

1. An electrode material which is the following electrode material (A). Electrode material (A): The present invention comprises a porous composite support comprising a support skeleton made of mesoporous carbon and a support metal fixed to at least the inner pore surface of the inner pore surface and the outer pore surface of the mesoporous carbon, and electrode catalyst particles supported on the support metal, An electrode material, characterized in that a part or all of the electrode catalyst particles are supported within the pores of the mesoporous carbon via the support metal.

2. An electrode material which is the following electrode material (B): Electrode material (B): The support includes a support skeleton made of mesoporous carbon and an electrode catalyst composite fixed to at least the inner pore surface of the mesoporous carbon, The electrode material, wherein the electrode catalyst composite comprises electrode catalyst particles and a support metal, the support metal being present so as to fill spaces between the electrode catalyst particles.

3. 3. The electrode material according to claim 1, wherein the support metal is any metal selected from the group consisting of tantalum (Ta), tungsten (W), niobium (Nb) and tin (Sn), or an alloy containing any of these metals as a main component.

4. 4. The electrode material according to claim 3, wherein the support metal is tantalum (Ta) or a tantalum alloy.

5. 3. The electrode material according to claim 1, wherein the mesoporous carbon has interconnected pores in which some or all of the pores in a mesopore region are interconnected with the pores in an adjacent mesopore region.

6. 3. The electrode material according to claim 1, wherein the mesoporous carbon has a pore size of 3 nm or more and 40 nm or less.

7. 3. The electrode material according to claim 1, wherein the electrode catalyst particles are particles made of Pt or an alloy containing Pt.

8. An electrode comprising the electrode material according to claim 1 or 2 and a proton-conducting electrolyte material.

9. 9. A membrane electrode assembly comprising a solid polymer electrolyte membrane, a cathode bonded to one side of the solid polymer electrolyte membrane, and an anode bonded to the other side of the solid polymer electrolyte membrane, wherein either or both of the anode and the cathode are the electrodes according to claim 8.

10. A polymer electrolyte fuel cell comprising the membrane electrode assembly according to claim 9.

Citation Information

Patent Citations

  • Catalyst layer ink and manufacturing method of fuel cell

    JP2019207789A

  • Electrode catalyst for electrochemical device, electrode catalyst layer for electrochemical device, membrane / electrode assembly for electrochemical device, electrochemical device, manufacturing method of electrode catalyst for electrochemical device, and manufacturing method of membrane / electrode assembly for electrochemical device

    JP2020064852A

  • Fuel cell catalyst

    JP2020126816A

  • Ionomer coat catalyst and manufacturing method thereof, and protective material coated electrode catalyst and manufacturing method thereof

    JP2021082578A

  • Electrode catalyst for fuel cell, electrode catalyst layer of fuel cell, membrane / electrode assembly and fuel cell

    JP6931808B1